2017
DOI: 10.1007/978-1-4939-6840-4_8
|View full text |Cite
|
Sign up to set email alerts
|

qFlow Cytometry-Based Receptoromic Screening: A High-Throughput Quantification Approach Informing Biomarker Selection and Nanosensor Development

Abstract: Nanosensor-based detection of biomarkers can improve medical diagnosis; however, a critical factor in nanosensor development is deciding which biomarker to target, as most diseases present several biomarkers. Biomarker-targeting decisions can be informed via an understanding of biomarker expression. Currently, immunohistochemistry (IHC) is the accepted standard for profiling biomarker expression. While IHC provides a relative mapping of biomarker expression, it does not provide cell-by-cell readouts of biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 45 publications
2
42
0
Order By: Relevance
“…Cells were washed, centrifuged at 500 g twice with 4 ml stain buffer, and resuspended in 300 μl stain buffer. The precision and accuracy of quantitative flow (qFlow) cytometry profiling has been rigorously tested . An LSR Fortessa (BD) was used for cell data acquisition; BD FACSDIVA software was used for data processing; and FlowJo (TreeStar) software was used for data analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were washed, centrifuged at 500 g twice with 4 ml stain buffer, and resuspended in 300 μl stain buffer. The precision and accuracy of quantitative flow (qFlow) cytometry profiling has been rigorously tested . An LSR Fortessa (BD) was used for cell data acquisition; BD FACSDIVA software was used for data processing; and FlowJo (TreeStar) software was used for data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Developing diagnostic tools that enable accurate measurement of plasma membrane receptors, or “biomarker preserving diagnostics” is a necessary step toward precision medicine . Indeed, several cancers are marked by overexpression of receptors, second messaging signaling molecules, and other dysregulated biomarkers, so accurate measurements of these biomarkers would be effective for diagnostics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minced tissues were then incubated with 0.2% collagenase IV for 5 min at 4 • C. After the incubation, the collagenase-treated tissues were vortexed for 3-5 min with 1-min interval to achieve optimal tissue dissociation. Dissociated tissues were then added bovine serum albumin (BSA)-supplemented stain buffer [32], and filtered through cell strainers (size 70 µm) to ensure single-cell suspension. Cell suspensions were spun down at 500 ×g for 5 min, resuspended at 4 × 10 6 cells/mL in stain buffer, and then kept on ice until antibody staining.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that quantification of plasma membrane RTKs, including NRP1 and PDGFRβ, can be affected by enzymatic cell dissociation solution, such as TrypLE TM (Thermo Fisher Scientific, MA, USA) [5,32]. To assess the effect of the coculture dissociation protocol, which includes a 5-min incubation with collagenase IV and some rigorous mixing, we dissociated HUVEC and HDF monocultures using two methods: (1) The traditional method where HUVECs and HDFs monocultures were lifted and dissociated using a nonenzymatic dissociation buffer, CellStripper TM (Corning, NY, USA), as described previously [8,32]; (2) The coculture dissociation mimicry where CellStripper TM -lifted cells were incubated with HBSS with 2 mM EDTA (VWR, Chicago, IL, USA) and 0.2% BSA for 2-3 min, then with 0.2% collagenase IV for 5 min at 4 • C, vortexed for 3-5 min with 1-min interval, filtered through 70-µm cell strainers (Fisher Scientific, Hanover Park, IL, USA ) and resuspended in ice-cold stain buffer at 4 × 10 6 cells/mL. qFlow cytometry analysis showed insignificant differences of monoculture RTK concentrations between the coculture dissociation method and the traditional method ( Figure S2).…”
Section: Introductionmentioning
confidence: 99%